Relationship between body image, body dissatisfaction and weight status in Iranian adolescents - Hatami, Monireh; Mohd Taib, Mohd Nasir; Djazayery, Abolghassem; Mojani, Mansooreh Sadat; Mejlej, Fariborz Hamidi (Vernon Innovative Publishers, 2015)
Background: In current society adolescents are concerned about body image. The relationship between body dissatisfaction and obesity is not clear in developing countries. This study sought to describe body image size perception and dissatisfaction, and their relationship with body weight status in adolescents. Methods: Objective measures of weight and height were undertaken on 1109 schoolchildren aged 10-18 (504 girls and 605 boys). BMI z-scores, and weight status were calculated based on the 2007 WHO growth reference charts. Figure rating scales were used to assess perceptions of current and ideal body size and dissatisfaction difference between these perceptions. Multivariate analyses were used to assess the relationship between the perceptions and dissatisfaction with body weight status. Results: Perceived body image size was positively associated with weight status (partial regression coefficient for overweight/obese vs non-overweight/obese was 0.63 (95% CI 0.26-0.99) and for BMI z-score was 0.21 (95% CI 0.10-0.31), adjusted for sex and age). Body dissatisfaction was also associated with weight status, with overweight and obese children more likely to select thinner ideal body size than healthy weight children (adjusted partial regression coefficient for overweight/obese vs nonoverweight/ obese was 1.47 (95% CI 0.99-1.96) and for BMI z-score was 0.54 (95% CI 0.40-0.67). Conclusions: Awareness of body image size and increasing body dissatisfaction with the higher weight status is established at a young age in this population. This needs to be considered when designing interventions to reduce obesity in young children, in terms of both benefits and harms.